2013
DOI: 10.1016/j.eururo.2012.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy in Small Cell Urothelial Cancer Improves Pathologic Downstaging and Long-term Outcomes: Results from a Retrospective Study at the MD Anderson Cancer Center

Abstract: Background Small cell urothelial carcinoma (SCUC) is a rare, aggressive malignancy with a propensity for early microscopic metastases. Data suggest that neoadjuvant chemotherapy may lead to improved survival compared with initial surgery. Objective To determine the influence of neoadjuvant chemotherapy on survival of SCUC patients in a large single-institution cohort. Design, setting, and participants Between 1985 and 2010, 172 patients were treated for SCUC at MD Anderson Cancer Center (MDACC). Clinical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(123 citation statements)
references
References 14 publications
9
110
1
3
Order By: Relevance
“…21 These promising results were recently corroborated by another report from the MD Anderson group. 22 The substantial differences in OS of patients in the present study with bladder preserving strategy versus the mentioned cystectomy series might partly be explained by small sample sizes, differences in initial tumor stage, different regimens of chemotherapy and clinical versus pathological TNM staging. Patient selection might be another confounding factor.…”
Section: Discussionmentioning
confidence: 81%
“…21 These promising results were recently corroborated by another report from the MD Anderson group. 22 The substantial differences in OS of patients in the present study with bladder preserving strategy versus the mentioned cystectomy series might partly be explained by small sample sizes, differences in initial tumor stage, different regimens of chemotherapy and clinical versus pathological TNM staging. Patient selection might be another confounding factor.…”
Section: Discussionmentioning
confidence: 81%
“…8 More recently, MD Anderson Cancer Center investigators reported their results of a 25-year follow up of SCCB. 9 They analyzed the outcomes of 95 patients with SCCB, of which 48 underwent neoadjuvant chemotherapy followed by radical cystectomy and 47 underwent radical cystectomy. Neoadjuvant treatment was associated with improved OS and CSS compared with initial cystectomy (median OS 159.5 months vs 18.3 months, P < 0.001; 5-yr CSS 79% vs 20%, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…For ED, the recommendation is to administer regimens similar to those used in SCLC, such as cisplatin or carboplatin in combination with etoposide or irinotecan. 72 …”
Section: Treatmentmentioning
confidence: 99%
“…20,29,31,72 Siefker-Radtke and colleagues 31,29,72 advocate for combining chemotherapy with surgery based on retrospective and phase II studies.…”
Section: Neoadjuvant and Adjuvant Chemotherapy With Surgerymentioning
confidence: 99%
See 1 more Smart Citation